370 The CO-existence of KCNQ1 and TNNI3 genes mutations supports the genetic origin of QTC abnormalities in hypertrophic cardiomyopathy. (17th December 2020) - Cava, Francesco; Cristiano, Ernesto; Lo Monaco, Maria; Musumeci, Maria Beatrice; Savio, Camilla; Petrucci, Simona; Rubattu, Speranza Donatella; Piane, Maria; Autore, Camillo
Abstract: Hypertrophic cardiomyopathy (HCM) and Long QT Syndrome (LQTS) are inherited diseases characterized by a wide genetic heterogeneity. Based on the separate incidence of these pathologies and on the absence of linkage, the occurrence of both diseases in the same individual has an incidence of about 1/250000. We describe a rare case report of a 24 years-old patient with maternal familiarity for type 1 LQTS (mother carrier of KCNQ1 c.1781G>A) and paternal familiarity for HCM (father carrier of TNNI3 c.592C>G mutation) who inherited both gene mutations and was diagnosed with HCM and LQTS later in adolescence, after clinical and genetic evaluations.